The Art of Attentive Teaching : Mediated Interaction, Dynamic Learning and Thinking Journey - Schur, Yaron, (Educational Research E-Books Online, Collection 2026, 2026)
The Art of Attentive Teaching presents an innovative, creative and optimistic pedagogical approach based on recognizing every individual's ability to acquire knowledge and understanding, while experiencing positive and enriching learning. Assuming that each and every learner experiences a unique set of learning processes in subject matter learning, teaching them has to be tailored to each and every learner's needs. This may seem impossible, especially in large, overcrowded classes. However, combining theory and practice, in this book you will find a variety of examples from different disciplines and ages, showing that with Attentive Teaching it is indeed possible to achieve this.